Association of vitamin E intake in diet and supplements with risk of dementia: A meta-analysis - Rangyin Zhao; Rangyin Zhao; Xiaoyong Han; Hongxia Zhang; Jia Liu; Min Zhang; Weijing Zhao; Shangrong Jiang; Ruilin Li; Hui Cai; Hui Cai; Hui Cai; et al. (Frontiers in Aging Neuroscience, 2022)
BackgroundDementia is a chronic progressive neurodegenerative disease that can lead to disability and death in humans, but there is still no effective prevention and treatment. Due to the neuroprotective effects of vitamin E, a large number of researchers have explored whether vitamin E can reduce the risk of dementia. Some researchers believe that vitamin E can reduce the risk of dementia, while others hold the opposite conclusion. We therefore performed a meta-analysis to clarify the relationship between them.MethodsWe searched PubMed, Embase, and Web of Science databases for articles on the connection of dietary and supplementation vitamin E with dementia risk from inception through April 2022 using the main keywords “dementia,” “Alzheimer's disease,” “vitamin E,” and “tocopherol,” and used a random-utility model for pooled effect sizes. Odds ratios (OR) and 95% confidence intervals were derived using lower and higher doses as contrasts. Obtained data were shown and assessed using Stata12.0 free software.ResultsWe included 15 articles in sum. Among them, there were nine articles containing AD. By comparing the highest intake with the lowest intake, Combined ORs for high intake were as follows: dementia (OR = 0.79, 95% CI 0.70–0.88 I2 = 35.0%), Alzheimer's disease (OR = 0.78, 95% CI 0.64–0.94 I2 = 36.9%). Subgroup analyses were also performed by study type, diet and supplementation, and NOS score.ConclusionsHigh vitamin E intake from diet and supplements significantly reduces the risk of dementia and Alzheimer's disease.